Muscle activity and airflow dynamics upon gradual weight-gain volumetric enlargement or acute surgical reduction of the tongue base during chewing and swallowing - Doris Haydee Rosero Salazar; Edward M. Weaver; Zi-Jun Liu (PLoS ONE, 2026)
We aimed to understand changes in activity of oropharyngeal muscles and respiratory airflow during chewing and swallowing in two clinically important conditions: gradual weight-gain volumetric enlargement and acute surgical reduction of the tongue base. Six same-sex sibling pairs of 8-to-9-month-old Yucatan minipigs, 3-each-sex, were studied. Of each pair one was fed with high-calorie pellets to reach obesity with a BMI > 50 (enlargement group), and the other was normal-weighted (BMI < 38) and underwent surgical volumetric reduction of the tongue base (reduction group). Electromyograms (EMG) of the tongue (genioglossus and styloglossus), palatal (tensor veli palatini and levator veli palatini), hyoid/pharyngeal (thyrohyoid and middle pharyngeal constrictor), and jaw (masseter and digastric) muscles were recorded simultaneously with respiratory airflow monitoring and x-ray videofluoroscopy during unrestrained feeding of pellets mixed with barium-sulfate. Videofluoroscopic images and activity-bursts of the digastric and thyrohyoid muscles were references to detect chewing cycles and swallowing episodes. Recording sessions for both groups occurred at baseline (before surgery in reduction group), and weeks 1, 3, and 5 (after surgery in reduction group). EMG activity amplitudes, burst-durations, onsets (timings of muscle activity), and respiratory airflow were evaluated. Altered chewing EMG included delayed onsets of the tensor veli palatini and styloglossus in both groups at weeks 1, 3, and 5 compared to the baseline (p < 0.05). In addition, the activity amplitudes of the styloglossus and masseter muscles in the enlargement group were higher in comparison to those of the reduction group (p < 0.05). Effects on swallowing involved delayed timings of the palatal and tongue muscle activities in the reduction group with potential impaired swallowing after surgery. The enlargement group was susceptible to breathing alterations evidenced by decreased airflow velocity, airflow pressure and tidal volumes in comparison to those of the reduction group (p < 0.05). These findings reveal adaptations to ensure synchronized feeding and respiration under volumetric alterations of the tongue base, with risks of impaired swallowing and respiratory patency.